2011
DOI: 10.1111/j.1600-9657.2011.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of maxillofacial fractures at a tertiary hospital in northern India: a 4-year retrospective study of 718 patients

Abstract: Better socio-economic status of people, increased vehicular movements and non-implementation of road safety norms have increased road traffic accidents. Proper education of the people who are most commonly involved in the RTA can be one of the possible ways to reduce the maxillofacial injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
57
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 16 publications
13
57
1
4
Order By: Relevance
“…. The explanation for the increase if interpersonal violence is higher alcohol consumption, drug abuse and social disparities due to unequal wealth distribution 1,16,17 . It was found that skin color, a marker of social inequality, 5,6 represents a risk factor for facial traumas, since black and brown victims tended to have more lesions in the middle third of the face.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. The explanation for the increase if interpersonal violence is higher alcohol consumption, drug abuse and social disparities due to unequal wealth distribution 1,16,17 . It was found that skin color, a marker of social inequality, 5,6 represents a risk factor for facial traumas, since black and brown victims tended to have more lesions in the middle third of the face.…”
Section: Discussionmentioning
confidence: 99%
“…The face is usually the first area to be damaged in case of physical aggression, car accidents and falls, which makes the maxillofacial region very susceptible to traumas due to its prominence 1 . Traumas of the maxillofacial complex represent one of the most important health problems worldwide, especially because of the high incidence and the diversity of facial lesions 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies were published recently investigating the incidence and causes of facial-bone-trauma and prevalence of zygoma-tripod, -quadripod, -arch and orbital floor-fractures in the growing elderly population of 70 years + in various parts of the world [6][7][8][9][10][11] but only isolated studies suggest therapy-guidelines for treatment modalities in this increasing patient-group with mostly general chronic-disease anamnesis [12,13] which should be based on a multidisciplinary…”
Section: Introductionmentioning
confidence: 99%
“…1 -2,7 mm) and no fracture-stages/fracture-crepitations/maxillary mobility palpable in clinical investigation (Figure 2) b) Fractures with dislocations above critical-size-defects (2,7mm [17]) and/or fracture-stages/fracture-crepitations/maxillary mobility palpable in clinical investigation ( Figure 3) According to the category of the fracture-classification, patients were sorted into two therapy-groups from the CMF-surgeons point of view, basically with a less invasive approach than proposed in the literature [18,19]. Basically a more conservative surgical treatment approach was followed [8,9] in favour of only closed transcutaneous fracture reduction [20] and only optional open reduction, osteosynthesis and orbital-floor-reconstruction.…”
mentioning
confidence: 99%